Tratamiento contable y tributario de los ingresos por contratos de clientes en las empresas del sector salud - Pazos Quinto, Jorge Xavier (2021)
Revenue recognition from contracts with customers and accrual accounting in health care entities are set in order to fulfil the objectives of the financial accounting standards allowed in this country. Few prepaid financing companies are aimed at the health care industry in Ecuador (Acuerdo Ministerial N 5212). Thus, currently it has come into existence 21 authorized entities allowed to provide prepaid health care fees. Indeed, this project seeks the implementation of the financial accounting standards, safeguarding the cash flow as well; that is essential foundations to stay in the market……..